Bringing the Material to Life: Therapeutic Recreation Process Case Study Folder Assignment for Undergraduate Students. Issue 1 (1st January 2017) - Berbary, Lisbeth A.
Abstract: In undergraduate courses, case studies are often used to bring material to life for students in ways that allow them to connect theory to applied practice. Case studies can be of particular use in Therapeutic Recreation courses, where students are able to obtain a glimpse into the complex thinking that must occur when working with participants with/in community. The following Assessment, Planning, Implementation, and Evaluation (APIE) TR process case study was designed to provide students with introductory level knowledge on the intense, deliberate, and meaningful planning that must go into designing innovative, social justice oriented, TR programming for individuals with/in communities.